Answer:
![f(-6)=14](https://tex.z-dn.net/?f=f%28-6%29%3D14)
Step-by-step explanation:
According to the remainder theorem, if a function f(x) is divided by (x-a), then the remainder is defined by f(a).
It is given that
has a remainder of 14.
Here, the function f(x) is divided by (x+6). So, on comparing (x+6) and (x-a), we get
![a=-6](https://tex.z-dn.net/?f=a%3D-6)
So, by remainder theorem, remainder of
is f(-6).
Since the remainder is 14, therefore
![f(-6)=14](https://tex.z-dn.net/?f=f%28-6%29%3D14)
Therefore, the answer for first blank is -6 and for second blank is 14, i.e.,
.